2009
DOI: 10.1002/art.24483
|View full text |Cite
|
Sign up to set email alerts
|

The early disease stage in axial spondylarthritis: Results from the german spondyloarthritis inception cohort

Abstract: Objective. Ankylosing spondylitis (AS) is diagnosed late, because radiographs of the sacroiliac joints often do not show definite sacroiliitis at the time of disease onset. The aim of this study was to investigate whether patients without definite radiographically defined sacroiliitis, referred to as nonradiographic axial spondylarthritis (SpA), are different from patients with AS with regard to clinical manifestations and disease activity measures. Moreover, we sought to identify determinants of the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

59
424
15
53

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 649 publications
(551 citation statements)
references
References 36 publications
(38 reference statements)
59
424
15
53
Order By: Relevance
“…Therefore, the majority of the patients did not develop radiographic changes, and 23% went into remission. Another study compared 2 patient groups with inflammatory back pain who either had structural changes in the SI joint or did not have structural changes in the SI joint (11). Of interest, there was no evidence that the latter group of patients had a milder disease course or less severe clinical symptoms; however, using the new criteria, patients with axial SpA who have structural changes (AS) or not (nr-axSpA) have not been directly compared.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the majority of the patients did not develop radiographic changes, and 23% went into remission. Another study compared 2 patient groups with inflammatory back pain who either had structural changes in the SI joint or did not have structural changes in the SI joint (11). Of interest, there was no evidence that the latter group of patients had a milder disease course or less severe clinical symptoms; however, using the new criteria, patients with axial SpA who have structural changes (AS) or not (nr-axSpA) have not been directly compared.…”
Section: Introductionmentioning
confidence: 99%
“…However one of the most important advances in the clinical understanding of AS has been the recognition of the significant time delay between the onset of symptoms, i.e., inflammatory back pain, and the development of radiographic evidence of sacroiliac joint damage, which can take an average of eight to ten years to become detectable. Furthermore, recent studies have shown that patients in the early stages of disease, prior to the appearance of radiographic sacroiliitis, have just as much pain, stiffness and functional limitation as those with established or radiographic AS [2]. This has led to increasing interest in the use of magnetic resonance (MR) imaging to detect changes at the sacroiliac joint or spine at an earlier stage.…”
Section: Mri In the Diagnosis And Classification Of Asmentioning
confidence: 99%
“…Sacroiliac pain may irradiate to the back, buttocks, groin and lower extremity similarly to pain patterns originating from other lumbosacral regions (Table 1). However, there is still a delay of years from the first symptoms until the final diagnosis is established [4]. Radiological changes are often detectable only years after the onset of AS, despite the presence of inflammation and clinical manifestations, such as pain and stiffness ( Figure 1) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%